1985
DOI: 10.1111/j.1399-0004.1985.tb01219.x
|View full text |Cite
|
Sign up to set email alerts
|

The facio‐audio‐symphalangism syndrome: report of a case and review of the literature

Abstract: A detailed account is given of a 5‐year‐old girl with the facio‐audio‐symphalangism syndrome. This genetic disorder has been known previously by other names, including the WL syndrome. The reasons for suggesting this new descriptive term are given, along with a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Multiple synostoses syndrome has also been described as WL symphalangism‐brachydactyly syndrome [Herrmann, 1974; Higashi and Inoue, 1983] and facioaudiosymphalangism [Hurvitz et al, 1985; van den Ende et al, 2005]. Linkage analysis of a family with multiple synostoses syndrome mapped to the same locus (17q21–q22) as proximal symphalangism [Krakow et al, 1998], and mutations in the NOG gene were later described in several families with multiple synostoses syndrome [Dawson et al, 2006; Debeer et al, 2005; Emery et al, 2009; Gong et al, 1999; Takahashi et al, 2001] (Table 1).…”
Section: Phenotypesmentioning
confidence: 99%
“…Multiple synostoses syndrome has also been described as WL symphalangism‐brachydactyly syndrome [Herrmann, 1974; Higashi and Inoue, 1983] and facioaudiosymphalangism [Hurvitz et al, 1985; van den Ende et al, 2005]. Linkage analysis of a family with multiple synostoses syndrome mapped to the same locus (17q21–q22) as proximal symphalangism [Krakow et al, 1998], and mutations in the NOG gene were later described in several families with multiple synostoses syndrome [Dawson et al, 2006; Debeer et al, 2005; Emery et al, 2009; Gong et al, 1999; Takahashi et al, 2001] (Table 1).…”
Section: Phenotypesmentioning
confidence: 99%
“…These syndromes were first reported by Cushing (Cushing, 1915) and Vesell (Vessel, 1960). In 1990, similar overlapping clinical syndromes were recognized as stapes ankylosis with broad thumbs and toes (SABTT), which is also known as TeunisseneCremer syndrome (Teunissen and Cremers, 1990), proximal symphalangism (SYM1) (Hurvitz et al, 1985), multiple synostoses syndrome 1(SYNS1) (Da-Silva et al, 1984), tarsal-carpal coalition syndrome (TCC) and brachydactyly type B2 (BDB2). These syndromes were thought to be non-identical at first, but direct sequence analysis of genes showed that mutations in NOG induce these syndromes, which are typical phenotypes of NOG mutations.…”
Section: Introductionmentioning
confidence: 96%
“…This gene encodes a secreted protein, noggin, a bone morphogenetic protein antagonist essential for normal bone and joint development in humans and mice. 3 NOG gene mutations leading to aberrant functions of the noggin protein have been found in some syndromes involving digital anomalies, including SYM1, 1 multiple synostosis syndrome (SYNS1), 4 facioaudiosymphalangism, 5 tarsal-carpal coalition syndrome, 6,7 stapes ankylosis with broad thumb and toes (SABTT) 8 and brachydactyly type B2. 9 Because these syndromes share several overlapping features, it is sometimes difficult to reach an exact diagnosis.…”
Section: Introductionmentioning
confidence: 99%